Schirmer tear test type I readings and intraocular pressure values assessed by applanation tonometry (Tonopen® XL) in normal eyes of four European species of birds of prey. (23rd November 2012) - Barsotti, Giovanni; Briganti, Angela; Spratte, Johanna R.; Ceccherelli, Renato; Breghi, Gloria
Abstract: Objective: To determine normal values for Schirmer tear test I and intraocular pressure in four European species of birds of prey. Animals studied: Twenty birds from each of the following species: Eurasian Tawny owl ( Strix aluco ), Little owl ( Athene noctua ), Common buzzard ( Buteo buteo ), and European kestrel ( Falco tinnunculus ). Procedures: Both eyes of all birds (80 eyes) underwent a complete ophthalmic examination, which included a Schirmer tear test type I (STT‐ I ) performed with commercially available strips and the assessment of the intraocular pressure (IOP) by applanation tonometry, employing the Tonopen‐XL ® device. The animals, which had been taken to a rescue center, were examined for ocular lesions prior to their eventual release into the wild. STT‐ I readings and IOP values were expressed as means ± standard deviation. Results: Schirmer tear test type I readings were as follows: Eurasian Tawny owls: 3.12 ± 1.92 mm/min; Little owls: 3.5 ± 1.96 mm/min; Common buzzards: 12.47 ± 2.66 mm/min; European kestrels: 6.20 ± 3.67 mm/min. IOP values were as follows: Eurasian Tawny owls: 11.21 ± 3.12 mmHg; Little owls: 9.83 ± 3.41 mmHg; Common buzzards: 17.2 ± 3.53 mmHg; European kestrels: 8.53 ± 1.59 mmHg. Conclusions: The results of this study give representative values for STT‐ I and IOP in four of the most common species of birds of prey in Europe.